2005
DOI: 10.1152/ajpcell.00098.2005
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+/calmodulin-dependent protein kinase IV activates cysteine-rich protein 1 through adjacent CRE and CArG elements

Abstract: Smooth muscle-specific transcription is controlled by a multitude of transcriptional regulators that cooperate to drive expression in a temporospatial manner. Previous analysis of the cysteine-rich protein 1 (CRP1/Csrp) gene revealed an intronic enhancer that is sufficient for expression in arterial smooth muscle cells and requires a serum response factor-binding CArG element for activity. The presence of a CArG box in smooth muscle regulatory regions is practically invariant; however, it stands to reason that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 59 publications
3
12
0
Order By: Relevance
“…The ability of the wildtype and Csrp1 −/− cells to activate the SMA-reporter was SRF-dependent, as a SMA-reporter with a mutated CArG was not induced in either cell type by TGF-beta. Consistent with our studies with the SMA reporter, a luciferase reporter containing 3 copies of the intronic CArG element from the Csrp1 gene 12, 26 was also upregulated by TGF-beta in the WT and Csrp1 −/− cells, while the Csrp2 −/− cells were unresponsive (supplementary data, Figure S1, panel A). …”
Section: Resultssupporting
confidence: 89%
“…The ability of the wildtype and Csrp1 −/− cells to activate the SMA-reporter was SRF-dependent, as a SMA-reporter with a mutated CArG was not induced in either cell type by TGF-beta. Consistent with our studies with the SMA reporter, a luciferase reporter containing 3 copies of the intronic CArG element from the Csrp1 gene 12, 26 was also upregulated by TGF-beta in the WT and Csrp1 −/− cells, while the Csrp2 −/− cells were unresponsive (supplementary data, Figure S1, panel A). …”
Section: Resultssupporting
confidence: 89%
“…This observation likely explains the absence of widespread MEF2 activation in vivo following vascular injury. Of the various CaMKs, CaMKII␦ appears to be the most likely kinase involved in c-Jun induction, given that recent evidence has demonstrated a critical role of this isoform during neointima formation, whereas CaMKIV has been implicated in VSMC differentiation (55,56). In addition, we demonstrate that PKA can enhance the repression of c-jun by increasing the nuclear localization of HDAC4 through inhibition of SIK1.…”
Section: Discussionsupporting
confidence: 51%
“…Although several transcriptional mechanisms have been identified for the Ca 2ϩ -dependent dendritic arborization, few transcriptionally regulated effectors have been reported. In smooth muscle cells, CRP1 expression is increased after depolarization induced by high K ϩ (Najwer and Lilly, 2005), suggesting that CRP1 may be involved in postdepolarization modifications. Because our data showed that CRP1 is required for dendritic growth in neurons, we hypothesized that CRP1 may act as a mediator for dendritic growth induced by Ca 2ϩ influx.…”
Section: Crp1 Is Upregulated By Camentioning
confidence: 99%